A corrente intermediária e a omissão específica da responsabilidade civil do estado por omissão no direito brasileiro - Mota, Caio Poderoso Bispo da (2021)
The Civil Liability of the State, when it comes to State omission, is still a topic that raises several dabates among jurists, national and international. There are doctrines that maintain that this will always be objective, regardless of the circumstances, whether by action or inaction of the State, as a result of the constitutional provision. However, the majority doctrine defends another thought, that the responsability of the Public Administration for omissive acts should be always subjective, based on the theory anonymous fault of the service, or faute du service. However, there is a third current, which began in the middle of this decade to gain space within national jurisprudence and doctrine, which states that it is possible to have both types of State accountability in case of omission, and it should be noted in the specific case if an specific omission or a generic omission. Even so, although it has already been used as a basis in judgements even by STF, this doctrine ir not yet the majority in our country, being defended by a samall portion of scholars, in addintion, it is only applied in specific cases in the courts